Etude théorique et comparative de différentes familles de composés chimiques : Clusters de Bor et Carboranes apparentés, complexes organométalliques et composés organiques biologiquement actifs - Benyza, Nabil (Universty of Eloued جامعة الشهيد حمه لخضر, 2019)
الملخص: يهدف العمل المقدم في هذه الرسالة الى دراسة نظرية ومقارنتها بما وجد تجريبيا لعائلتين من المركبات الكيميائية ويتعلق الامر ب: مركبات البور ومشتقاتها الكاربوران ذات الصيغة العامة (CRnRBR13-nRHR13RP n-2 P و المعقدات العضوية المعدنية ذات الصيغة العامة / n= 0, 1, 2 et 3) [M (L) R2RP + 2 P.2 (ClO4)P - Pمع مستويات Cu ،Co ،Ni ، Cr, Mn ،Fe [ حيث المعدن هو BR13RHR13RP مختلفة من الحسابات النظرية. قمنا أولا بدراسة نظرية للمركبات -2 ومشتقاتها الكاربوران P (CRnRBR13-nRHR13RP 2 و 3. أظهرت الحسابات المتعلقة بتحسين الهيئة , يأخذ القيم 1 n اين العدد P لمتما كبات المركبات المدروسة التي تم تحديدها وفقاً للمواضع المختلفة لذرات الكربون وجود اتفاق بين النتائج التي تم الحصول عليها والنتائج التجريبية. بعد ذلك قمنا بإجراء دراسة مقارنة على المعقدات المذكورة سابقا. تظهر حساباتنا وتؤكد وجود اتفاق جيد جدا بين الدراسة التجريبية والدراسة النظرية n-2 . النتائج التي تم العثور عليها نظرياً للأنظمة الافتراضية المدروسة ، لا سيما المخططات الطاقوية للمدارات الجزيئية ، اظهرت ان هذ ه المركبات لها فعالية كيميائية كبيرة. اما ما تعلق بالدراسة الاهتزازية فقد اكدت هذه الاخيرة أن كل المركبات المدروسة هي حالات استقرارية وهذا مؤكد من خلال قيم الترددات النظرية للاهتزاز حيث انها كلها حقيقية. ABSTRACT: The work presented in this thesis concerns a theoretical and comparative study of two class of chemical compounds: boron clusters and their derivatives (carborane) of général formula (CRnRBR13-nRHR13RP n-2 P / n= 0, 1, 2 et 3) and the Organometallic complexes which have the formula [M(L)2+2.2(ClO4)-] / M = Mn, Fe, Cr, Ni, Co, Cu. at different levels of quantum chemical computations. In beginning a theoretical study of the cluster BR13RHR13RP 2- P and their carborane derivatives (CRnRBR13-nRHR13RP n-2 P / n = 1, 2 and 3). Calculations concerning the optimization of geometry’s (bond lengths and bond angles) have shown a good agreement between the results obtained by quantum chemical computations and experimental results. Subsequently we performed a comparative study on organométallic complexes. Our calculation’s show and confirm the existence of a very good agreement between the experimental study and the theoretical study. The results found theoretically for hypothetical systems, particularly the molecular orbital diagrams (FOM), show the chemical reactivity of these systems. Concerning the vibrational study we note that the studied complexes are stationary states this due to the values of the theoretical frequencies of vibration, which are all real.
Thèse de Doctorat Spécialité :Thése Doctorat en Sciences Option Chimie physique
Keywords: B3LYP ،DFT مركبات البوران ، الكربوران ، المعقدات العضوية المعدنية; cluster of boron, carboran, DFT, B3LYP, organometallic complex, electronic structure